Generalized Derivations of BF-Algebras - Mohammed Khalid Shahoodh (Academic Science Journal)
In this paper, we introduced the concept of generalized derivations of an algebraic structure namely BF-algebras and studied some of its basic properties. Moreover, some results that concern on the kernel of the generalized derivations of a BF-algebras are presented. Furthermore, we studied the concept of torsion free on a BF-algebras.